Compressible and robust PANI sponge anchored with erected MXene flakes for human motion detection. (December 2021) - Chang, Kangqi; Li, Le; Zhang, Chao; Ma, Piming; Dong, Weifu; Huang, Yunpeng; Liu, Tianxi
Abstract: Advanced pressure sensors featuring high compressibility, high sensitivity, fast response time, and superior stability have attracted tremendous research attention because of their potential applications in artificial intelligence technology and wearable electronics. In this work, a robust sponge-like piezoresistive pressure sensor with remarkable elasticity and high sensitivity was fabricated by anchoring perpendicularly oriented MXene flakes on polyaniline (PANI) wrapped polymeric sponge via freeze-drying-assisted depositing strategy. Owing to the stable 3D conducting networks provided by PANI sponge and the intimate electrical contact between erected MXene flakes upon subtle deformation, good sensitivity, wide working range, low detection limit, fast response and recovery times, and excellent durability can be simultaneously obtained. Furthermore, various physiological activities (speech recognition, swallowing, joint movement, etc.) can also be detected in real-time and wireless manner by the flexible MXene/PANI sponge sensors, demonstrating their great potential in low-cost and high-performance wearable piezoresistive pressure sensing devices.